Mindful Parenting Mothers with Middle Childhood Age during the Covid-19 Pandemic - Husnul Khotimah (Universitas Nusa Cendana, 2022)
Accompanying children school from home for mothers with middle childhood age is one of the most challenging tasks for mothers, leaving them vulnerable to physical and psychological exhaustion. Mindful parenting is one way to reduce negative parenting. This study aims to obtain an overview of mindful parenting in terms of demographic factors. Research respondents are mothers with middle childhood age of 242 respondents using accidental sampling technique. The research instrument used a mindful parenting scale consisting of 31 items, with descriptive and chi square data analysis. The results showed that the mother's demographic factors, including age, education level and employment status of the mother could not predict the mother's mindful parenting.